FGL1 as a Novel Mediator and Biomarker of Malignant Progression in Clear Cell Renal Cell Carcinoma - Lv, Zheng; Cui, Bo; Huang, Xing; Feng, Hua-Yi; Wang, Tao; Wang, Han-Feng; Xuan, Yun-Dong; Li, Hong-Zhao; Ma, Xin; Huang, Yan; Zhang, Xu (Frontiers in Oncology, 2021)
Patients with clear cell renal cell carcinoma (ccRCC) have a poor prognosis. Emerging strategies for enhancing the immune response in ccRCC therapy are currently being investigated. By binding LAG-3 and negatively regulating T cells, fibrinogen-like Protein 1 (FGL1) is involved in tumor immune escape. This study aimed at investigating underlying mechanisms of FGL1 in ccRCC, and its expression and prognostic value. FGL1 was found to be upregulated in tumor tissues and plasma specimens of ccRCC patients. High FGL1 expression predicted a poor prognosis for ccRCC patients. We also discovered that overexpression of FGL1 enhances progression of RCC by activating epithelial to mesenchymal transition (EMT). Consistently, correlations between expressions of FGL1 and EMT-related genes were significantly positive, as determined by tissue microarray analysis. Gene-expression analysis revealed that FGL1-deficient ccRCC cell lines had altered transcriptional output in inflammatory response, cell-cell signaling, negative T cell activation regulation, and intracellular signal transduction. Depletion of FGL1 significantly inhibited tumor growth as well as lung metastasis in orthotopic xenograft mice models. Infiltration of myeloid-derived CD11b+ and Ly6G+ immune cells in the tumor microenvironment (TME) was strikingly decreased when FGL1 expression reduced. Therefore, increased FGL1 expression in ccRCC is positively correlated with poor prognosis. Mechanistically, FGL1 facilitates the EMT process and modulates TME, which promotes ccRCC progression and metastasis. Consequently, targeting FGL1 can potentially improve clinical outcome of ccRCC patients.